2002
DOI: 10.1029/2002jd002506
|View full text |Cite
|
Sign up to set email alerts
|

Surface tension of Rax cloud water and its relation to the concentration of organic material

Abstract: [1] During an intensive field campaign at a midlevel (1640 m above sea level) mountain in central Europe, cloud water samples were collected using a cloud water sampler and subsequently analyzed for organic and inorganic ions, total carbon (TC), and black carbon (BC). Cloud water surface tension (s) was measured using the ring method. Generally, the cloud water samples had surface tensions lower than that of pure water. The average value of s was 95.2% of the s of water, while the lowest value was 83.3%. A tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…In addition to their influence on the amount of mass in solution, organics might also change the surface tension of the particles. It has been shown that this effect might be small for short‐chain mono‐ and dicarboxylic acids [ Shulman et al , 1996] but is more distinct in the presence of high molecular weight acids with many functional groups [ Facchini et al , 2000; Hitzenberger et al , 2002]. These compounds reduce the surface tension, leading to enhanced drop growth rates [ Gorbunov et al , 1998; Nenes et al , 2002].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their influence on the amount of mass in solution, organics might also change the surface tension of the particles. It has been shown that this effect might be small for short‐chain mono‐ and dicarboxylic acids [ Shulman et al , 1996] but is more distinct in the presence of high molecular weight acids with many functional groups [ Facchini et al , 2000; Hitzenberger et al , 2002]. These compounds reduce the surface tension, leading to enhanced drop growth rates [ Gorbunov et al , 1998; Nenes et al , 2002].…”
Section: Introductionmentioning
confidence: 99%
“…Simple theory indicates that S c is anticorrelated with the number of soluble ions in the particle and, hence, is dependent on particle composition and size. Changes in critical supersaturation and droplet growth characteristics may be introduced by partly soluble substances, soluble gases, and surface tension effects [ Shulman et al , 1996; Hitzenberger et al , 2002; Charlson et al , 2001].…”
Section: Introductionmentioning
confidence: 99%
“…The correction factor depends strongly on the particle size and the surface tension of the considered aerosol particle/droplet. The surface tension varies with the composition of the aerosol particle (Facchini et al, 1999;Hitzenberger et al, 2002;Ervens et al, 2004Ervens et al, , 2005; e.g., it is increased by dissolved salts (Seinfeld and Pandis, 2006) and decreased by organic compounds (Facchini et al, 1999;Ervens et al, 2005). However, for the estimation of the vapor pressures for the partitioning compounds a group contribution method (EVAPORATION, Compernolle et al, 2011) is applied in this study.…”
Section: Limitations Of the Present Studiesmentioning
confidence: 99%